MAKNA DAN HAMBATAN PEMERANAN TANDAK LUDRUK : ANALISIS SEMIOTIK - , Muhammad Dinu Imansyah; , Prof. Dr. C. Soebakdi Soemanto, S.U ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In ludruk, tandak is the male actor who plays female characters. The ludruk actors dressed and behaved like women to replace the original women's presence on stage. At the time of the birth of art ludruk, there are both religious and traditional Javanese norms prohibiting women to appear in public, especially at night. This study aims to analyze the system of signs (semiotics) imposed by the tandak actor in representing female figures in the ludruk show. The Theatrical sign system used is Tadeusz Kowzan system of signs that deal directly with the actors: the sign system of language, tone, gestures, facial expressions, movement, makeup, fashion and hairdressing. From the research conducted, the results obtained the eighth tandak systems utilizing these markers to represent the figures of women, among others: using utterances that show that she (he) is a woman (the sign language system)